Biomechanical study of two alternative methods for the treatment of vertical femoral neck fractures – A finite element analysis. (November 2021) - Xia, Yutong; Zhang, Wendong; Hu, Hai; Yan, Lianqi; Zhan, Shi; Wang, Jingcheng
Abstract: Background: No consensus has been reached for the treatment of vertical femoral neck fractures (vFNFs). Recently, two alternative methods were invented to treat vFNFs, one of which is a new plate with a sliding groove, which was designed as a substitution of the medial buttress locking plate to combine with cannulated compression screws (CCS) for reducing the breakage possibility of the proximal locking screw during the bone healing. Another one is the femoral neck system (FNS), which was believed with biomechanical superiority. This study aims to compare the biomechanics of these two new implants with three previous methods via finite element analysis (FEA) to validate whether they are suitable for the treatment of vFNFs. Methods: Five 70-degree Pauwels type III transcervical FNFs (vFNFs, AO/OTA 31B2.3 r ) models were built and fixed by CCS augmented with the newly designed sliding groove buttress plate (CCS+BS) and FNS. For comparison, models fixed by three parallel cannulated compression screws (CCS), biplane double-supported screw fixation (BDSF), CCS augmented with a medial buttress locking plate (CCS+BL) were also built. A 2100N load was applied along with the mechanical axis. Parameters of the maximal stress as well as the maximal displacement of the implants and bone, the maximal relative displacement of interfragments, and the stiffness, were analyzed to compare the biomechanical characteristics of the five models. Results: CCS+BS and CCS+BL showed stronger fixation strength with improved stiffness (1012.05N/mm, 1092.04N/mm), reduced maximal displacement of the implants (1.976mm, 1.838mm) and bone (2.075mm, 1.923mm), when compared with CCS (925.11N/mm, 2.158mm and 2.270mm) and BDSF (842.36N/mm, 2.299mm and 2.493mm). While FNS showed the weakest stiffness (593.22N/mm) and largest maximal displacement of the implants (3.234mm) and bone (3.540mm) among the five models. Conclusions: CCS+BS has a better biomechanical performance than CCS and BDSF, which offers a new choice to deal with vFNFs. The construction stability of FNS is weaker than CCS, BDSF, and CCS+BL, indicating that this method may not as stable as reported in the previous study. Highlights: Firstly, our study was the first one to elaborate the correct contact relationship of FNS in FEA, and another newly designed sliding groove medial buttress plate was also compared with three previous methods (CCS, BDSF, and CCS+BL), the results were meaningful. Secondly, our study found that CCS+BS has a better biomechanical performance than CCS and BDSF, which offers a new choice to deal with vFNFs. The construction stability of FNS is weaker than CCS, BDSF, and CCS+BL, indicating that this method may not as stable as reported in the previous study. Thirdly, previous studies have shown that the BDSF was more suitable than CCS for the treatment of femoral neck fracture. However, based on the results in this study, interfragmentary displacement of BDSF was observed larger than CSS showing that BDSF may not suitable in vertical femoral neck fractures. Nowadays, femoral neck fractures are highly increasing, the cost-effective mothed is urgently under require.